0037 Evaluation Of A New Simulation Programme For Medical Students – A Learning Experience For Faculty And Candidates. (1st November 2014) - Kamal-Uddin, Solomon; Malley, Michael; Ross, James
Abstract : Background/context: The Paediatric Department set up a programme for medical students that would promote leadership and management skills, simulation was chosen as an appropriate teaching modality. 1, 2 The Healthcare Leadership Competency Framework was used to identify desired leadership learning outcomes. 4 Groups of 10 students were paired for scenarios based on concepts of leadership within a clinical environment. 5 The evaluation assesses both learner and facilitator feedback with a view to improving the course and identifying lessons for design of future initiatives. Methodology: Feedback from medical students was collected via a pre and post course questionnaire looking highlighting leadership skills in the clinical setting. In addition the faculty were asked to provide feedback focused on the design, implementation and success of the course with a separate questionnaire. Results/outcomes: Initial Feedback was obtained from 25 medical students. It showed an increase in confidence across all leadership domains though further data is required for conclusions. However free text feedback indicated they had difficulty understanding what exactly the separate leadership domains were as phrased by the Healthcare Leadership Competency Framework. They also identified any exposure to simulation as beneficial and welcomed the focus on human factors. Facilitators identified four key themes: Low fidelity equipment helped focus on non-technical rather than clinical skills. Pre-existing scenarios generating appropriate discussion and feedback. It was hard providing feedback to individuals with a group size of 10. The Healthcare Leadership Competency framework confused, rather than supported, the design and evaluation of learning outcomes. 2 Conclusions and recommendations: Medical students welcome the opportunity to participate in simulation and learn about leadership and management skills. Low fidelity simulation can set up a programme that will test human factor skills. Problems may arise in utilising the current national leadership frameworks into relatable learning points and achievable objectives for medical trainee education. References: Spurgeon, P. Down, I (2010). Guidance for Undergraduate Medical Education: Integrating the Medical Leadership Competency Framework. Enhancing Engagement in Medical Leadership. NHS Institute for Innovation and Improvement and Academy of Medical Royal Colleges McGaghie W, Issenberg B, Petrusa E, Scalesse R. A critical review of simulation-based medical education research: 2003–2009. Med Educ 2010;44(1): 50–63 Arora S, Ahmed M, Paige J, et al . Objective Structured Assessment of Debriefing (OSAD): Bringing science to the art of debriefing in surgery. Annals of Surgery 2011